Optimizing ICARE-Based Blended Learning to Prepare Nurses for Competitiveness in the Modern Era: Literature Review - Ismailinar, Ismailinar; Isneini, Isneini (Poltekkes Kemenkes Aceh, 2025)
Background: The era of the Industrial Revolution 4.0 and Society 5.0 has driven significant changes in higher vocational nursing education to produce globally competitive graduates. In this context, blended learning is a learning strategy that enables the optimal integration of technology and innovation. The implementation of blended learning will be more effective when combined with the ICARE (Introduction, Connection, Application, Reflection, Extension) model because it is valid, practical, and student-centered. Purpose: To examine the effectiveness and potential optimization of the ICARE-based blended learning model in improving the competency and skills of nursing students. Methods: This study used a literature review design guided by the PRISMA flowchart. Data sources were obtained from databases such as Google Scholar, ScienceDirect, and ProQuest with the keywords: blended learning, ICARE model, and nursing competence. Selected articles met inclusion and exclusion criteria relevant to the topic of optimizing nursing vocational learning. Results: Six studies have shown that the implementation of the ICARE-based blended learning model consistently improves student engagement, critical thinking skills, clinical skills, and nurses' work readiness in professional practice settings. The integration of digital technology with a reflective and applied learning approach makes this model valid, practical, and appropriate for modern vocational education. Conclusion: The ICARE-based blended learning model has strong potential to improve the quality of learning, particularly in vocational and higher education.